Život a transcendence podle Hanse Jonase - Sokol, Jan (Lidé města, 2005)
Hans Jonas, an important German Jewish philosopher, is known in this country thanks to the translation of his book “Principal of responsibility” in which he attempted to deduce human responsibility for long-term effects of his/hers activities, namely as they relate to nature and environment. In his remarkable essay “Evolution and freedom” he introduces a method of his “philosophical biology” and reaches the extraordinary conclusion that life, excitability, and movement is not only prototypes, but also rather outright evolution roots eventually giving birth also to specific human freedom. Using this very important example, the Author presents his “non-reduction method”: Connection between metabolism and cell excitability on one hand and human freedom, on the other, does not mean that human is “nothing more than metabolism” and physiological determination. On contrary, more simple living forms may be understood as some undeveloped drowsing stadium and evolution stages of form of existence that we can and do experience personally, i.e. living with own dependent freedom, worries, understanding, and language.